Single-cell analyses identify bioengineered niches for enhanced maintenance of hematopoietic stem cells - Aline Roch (Nature Portfolio, 2017)
Haematopoietic stem cell (HSC) self-renewal is not sufficiently understood to recapitulate in vitro. Here, the authors generate gene signature and cell cycle hallmarks of single murine HSCs, and use identified endothelial receptors Esam and JamC as substrates to enhance HSC growth in engineered niches.